2008
DOI: 10.1073/pnas.0807840105
|View full text |Cite|
|
Sign up to set email alerts
|

A farnesyltransferase inhibitor prevents both the onset and late progression of cardiovascular disease in a progeria mouse model

Abstract: The authors note that the description of the dosing of farnesyltransferase inhibitor (FTI) tipifarnib was incorrect. The article states that the drug was delivered in mg/kg of mouse total body weight. However, the actual study design was based on the concentration of the FTI drug in the diet (mg of FTI mixed in 1 kg of transgenic mouse dough). This dosing protocol was based on prior pharmacokinetic data, and the biomarker data included in the paper shows the desired drug effects were achieved. This error does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
154
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 186 publications
(165 citation statements)
references
References 32 publications
10
154
0
1
Order By: Relevance
“…With increasing numbers of cell divisions, several phenotypes can be observed including nuclear blebbing, which is seen in primary fibroblasts from HGPS patients, along with a reduced growth rate and increased senescence in culture. 8,9 Of note, mutations in humans and mice that disrupt Zmpste24, resulting in permanent farnesylation of an otherwise normal lamin A, also give rise to phenotypes similar to HGPS, supporting the hypothesis that retention of the farnesylated C terminus leads to the cellular phenotype. 6,10,11 Therapeutic Strategies for HGPS Without treatment, HGPS is a uniformly fatal disorder.…”
Section: Hgpsmentioning
confidence: 78%
See 2 more Smart Citations
“…With increasing numbers of cell divisions, several phenotypes can be observed including nuclear blebbing, which is seen in primary fibroblasts from HGPS patients, along with a reduced growth rate and increased senescence in culture. 8,9 Of note, mutations in humans and mice that disrupt Zmpste24, resulting in permanent farnesylation of an otherwise normal lamin A, also give rise to phenotypes similar to HGPS, supporting the hypothesis that retention of the farnesylated C terminus leads to the cellular phenotype. 6,10,11 Therapeutic Strategies for HGPS Without treatment, HGPS is a uniformly fatal disorder.…”
Section: Hgpsmentioning
confidence: 78%
“…13,14 Furthermore FTIs improve phenotype and life span in mouse models of progeria. 9,15 It is thought that FTIs, by preventing farnesylation of progerin, reduce the accumulation of progerin at the nuclear rim, reducing the damaging effects of the mutant protein on the nucleus. 13 The outcome of an openlabel HGPS clinical trial of the FTI lonafarnib is awaited with great interest.…”
Section: Hgpsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5A,B). Nuclear blebbing has been considered the hallmark phenotype in HGPS cells, resulting from the abnormal anchorage of progerin to the inner nuclear membrane (Capell et al ., 2005, 2008; Dechat et al ., 2009, 2010). To assay MB's effects on nuclear morphology, mock‐ and MB‐treated cells were immunostained with antilamin A/C and antiprogerin antibodies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4F–J). Previous literatures reported that releasing progerin from the nuclear membrane by farnesyltransferase inhibitor treatment partially rescued the gene expression and morphological defects in HGPS cells (Capell et al ., 2005, 2008; Capell & Collins, 2006; Gelb et al ., 2006; Cao et al ., 2007; Wang et al ., 2007; Marji et al ., 2010). Indeed, we find that not only the nuclear morphology but also the chromatin organization and gene expression are improved in the MB‐treated HGPS nucleus (Fig.…”
Section: Discussionmentioning
confidence: 99%